2000
DOI: 10.1074/jbc.m001696200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of CCCH Zinc Finger Proteins with mRNA

Abstract: Macrophages derived from tristetraprolin (TTP)-deficient mice exhibited increased tumor necrosis factor ␣ (TNF␣) release as a consequence of increased stability of TNF␣ mRNA. TTP was then shown to destabilize TNF␣ mRNA after binding directly to the AU-rich region (ARE) of the 3-untranslated region of the TNF␣ mRNA. In mammals and in Xenopus, TTP is the prototype of a small family of three known zinc finger proteins containing two CCCH zinc fingers spaced 18 amino acids apart; a fourth more distantly related fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
166
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(170 citation statements)
references
References 31 publications
2
166
2
Order By: Relevance
“…As with classical loss-of-function tumor suppressor genes (Hanahan and Weinberg, 2000;Knudson, 2000), TTP or a closely related gene may be mutated in the tumor cells and transfection restores the missing function. We have sequenced the entire coding region of TTP and BRF1, a structurally related AREbinding zinc-finger protein that also regulates cytokine mRNA turnover (Lai et al, 2000;Stoecklin et al, 2002). In V2D1 tumor cells, no mutation was detected in either gene, and transcripts were of expected size and expressed at the same levels as in parental PB-3c cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with classical loss-of-function tumor suppressor genes (Hanahan and Weinberg, 2000;Knudson, 2000), TTP or a closely related gene may be mutated in the tumor cells and transfection restores the missing function. We have sequenced the entire coding region of TTP and BRF1, a structurally related AREbinding zinc-finger protein that also regulates cytokine mRNA turnover (Lai et al, 2000;Stoecklin et al, 2002). In V2D1 tumor cells, no mutation was detected in either gene, and transcripts were of expected size and expressed at the same levels as in parental PB-3c cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of mRNA stabilization is likely to involve ARE-binding proteins as adaptors between the signalling cascade and the decay machinery (Carballo et al, 2001;Mahtani et al, 2001). ARE-binding proteins with assigned functions in vivo include TTP, butyrate response factor-1 (BRF1) and AUF1, all of which promote degradation, as well as HuR that exerts an mRNA stabilizing effect (Carballo et al, 1998;Fan and Steitz, 1998;Peng et al, 1998;Loflin et al, 1999;Lai et al, 2000;Stoecklin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro selection of randomized RNA with recombinant TTP had yielded RNAs very similar to the prototype mRNA instability element, UUAUUUA(U/A)(U/A) (57). Comparison of the full-length TTP protein to its isolated RNA-binding domain (a 77-amino acid region containing the tandem TTP zinc fingers) has indicated that the RNA-binding ability and indeed the ability to destabilize tumor necrosis factor ␣ mRNA are maintained in the isolated RNA-binding domain (58). poly(U) can be used to deplete TTP from cellular extracts, thereby removing its mRNA destabilizing activity, suggesting this protein can bind well to poly(U) (17); however, competition experiments have suggested that poly(U) is not a strong target for TTP (59).…”
Section: Figmentioning
confidence: 99%
“…Human embryonic kidney 293 cells (referred to as 293 cells) were maintained, and transient transfection of 1.2 ϫ 10 6 cells with plasmid constructs in calcium phosphate precipitates was performed as described (20). In some experiments, pXGH5 (Nichols Institute Diagnostics, San Juan Capistrano, CA) was cotransfected to monitor transfection efficiency.…”
Section: Transfection Of Human Embryonic Kidney 293 Cells and Northermentioning
confidence: 99%
“…Apparently normal binding still occurs when the TTP protein is truncated to a 77-amino acid fragment containing the TZF domain and seven flanking residues on either side (20). By investigating the binding of RNA to TZF domains from various CCCH proteins, we have begun to characterize the extent of natural variation that can be tolerated and still maintain RNA-binding activity (20). In the present study, we have extended these findings by generating and testing a series of site-directed mutants of the TTP TZF domain.…”
mentioning
confidence: 99%